2018
DOI: 10.1007/s10570-018-1892-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chemical modification of wood in ionic liquids on the supermolecular structure and mechanical properties of wood/polypropylene composites

Abstract: Effects of chemical modification of wood with innovative ionic liquid on the supermolecular and morphology of wood/polypropylene composites were investigated using X-ray diffraction, hot stage optical microscopy, and differential scanning calorimetry. For the first time the chemical treatment of wood was conducted solely with newly synthesized ionic liquid, didecyldimethylammonium bis(trifluoromethylsulfonyl)imide. The modification was found to be responsible for significant changes in nucleating abilities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 60 publications
4
31
0
Order By: Relevance
“…Composites with the filler modified using the bifunctional system (EPP/silanes) are characterised by considerable amounts of the β-PP form, which is particularly evident for the PP + EPP-TEOS/OTEOS system. Literature sources [ 6 , 71 , 72 ] reported that this polymorphic form of polypropylene exhibits greater elasticity and increased impact strength compared to the α-PP form. Summing up, treatment of wood using the novel modification system generates the β-PP polymorphic form, which considerably influences values of strain and impact strength of the produced composite materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Composites with the filler modified using the bifunctional system (EPP/silanes) are characterised by considerable amounts of the β-PP form, which is particularly evident for the PP + EPP-TEOS/OTEOS system. Literature sources [ 6 , 71 , 72 ] reported that this polymorphic form of polypropylene exhibits greater elasticity and increased impact strength compared to the α-PP form. Summing up, treatment of wood using the novel modification system generates the β-PP polymorphic form, which considerably influences values of strain and impact strength of the produced composite materials.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, it is essential to introduce certain modifications in order to improve interface interactions in the composite system. Various methods are used to enhance compatibility between lignocellulose fillers and polymer matrices, e.g., chemical modification [ 4 , 5 , 6 ], surface grafting of polymers onto fillers [ 7 ], introduction of compatibilisers such as maleated polymer [ 8 ], and treatment with coupling agents [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, ionic liquids are used mainly to dissolve or modify biomass and cellulose (Brandt et al 2013;Ghasemi et al 2017;Borysiak et al 2018), but there is also a growing interest in the use of ionic liquids for the direct production of nanometric cellulose. Swatloski et al (2002) proved that cellulose can be dissolved, without any previous activation of pretreatment, in e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the stronger interphase interactions resulting from modification of wood with ILs are responsible for the increase of water stability in such composites. 26 Besides, synergic with the improved interfacial adhesion between the components, the presence of the hydrophobic ILs could act as a supplementary barrier for water penetration into the structure of the material. 25 The importance of this synergic mechanism is sustained by the fact that the IL-SCN can promote higher moisture stabilization for the WPCs in comparison with IL-Cl, probably due to its more pronounced hydrophobic character.…”
Section: Resultsmentioning
confidence: 99%
“…It can be stated that chemical modification of wood not only enhanced the adhesion between polymer matrix and filler but also limited the amount of voids present in the composites and thus had an effect on its dimensional stability. 25,26
Figure 7.Thickness swelling of untreated and IL-treated composite boards.
…”
Section: Resultsmentioning
confidence: 99%